Recent advances in solar tunnel dryer for performance improvement in food drying process: a review. (23rd July 2021) - Agarwal, Ankit Kumar; Rana, K.B.; Tripathi, B.
The unexpected increase in demand and persistent shortage of fossil fuels continues the search for an alternative source of power. Solar energy is one of the sustainable and renewable sources of power that encouraged various researchers from all over the world. The production of food and its immediate consumption is the biggest problem to reduce the wastages of food. To overcome the wastage, drying is an excellent method to preserve the food grains, fruits and vegetables. For drying, conventional drying system is sun drying which is free and a renewable source of energy. But, there are various limitations e.g. rain, dust, animals, wind and insects. The use of solar dryers can eliminate these limitations significantly and enhance the productivity of farmers towards better revenue earned. This review attempts to provide in brief the recent developments to increase the temperature of drying chamber and applications of drying technology for different foods and agricultural produce, with particular emphasis on the modifications in the dryer and process conditions. This review paper will be helpful to know about the recent trends and different useful aspects of solar tunnel dryer to the new researchers.